Free-Surface Vortices Mitigation using Anti-Vortex Plates in Dam Intakes through CFD - Manogaran T.; Mohd Arif Zainol M.R.R.; Wahab M.K.A.; Abdul Aziz M.S.; Abd Aziz N.; Zahari N.M.; Zawawi M.H.; Mohd Radzi M.R. (Semarak Ilmu Publishing, 2024)
By recording parameters such as velocity and volume fraction by contour plots or plane, a CFD model enables to analyse flow patterns in the model, such as free-surface vortices A free-surface vortex, a common problem may indeed be observed in a variety of submerged water intakes, notably shallow basins and low head intakes. These FSVs are likely to form an air-core vortex, eventually entrapping detritus and air pockets in the water intake system and causing further vibration and damage to the downstream turbine. When paired with a high velocity, the formation of vortices in the system been known to produce hydraulic transients, which cause unwanted operation or pressure changes. The model of the 1:100 scale dam reservoir was generated, computationally meshed, and modelled in FLUENT under ANSYS 2019 R3 at two different water levels to observe the FSV formations. To mitigate those FSV formations, anti-vortex plates with two distinct platessquare and wedgewere used. From the findings square plates outperform wedge plates because square it lowers the speed of a fast-flowing fluid and reduces it into a laminar flow rather of a turbulent flow, which benefits vortex class deterioration. Data from the simulation and experimental shows a strong agreement in terms of velocity at outlet 1 from both water levels with relative errors of 3.0% and 14.1% respectively. 2023, Semarak Ilmu Publishing. All rights reserved.